2021
DOI: 10.1002/nop2.1158
|View full text |Cite
|
Sign up to set email alerts
|

Association of social support, spirituality with psychological factors in Iranian breast cancer survivors: An evidence from a cross‐sectional study

Abstract: Breast cancer is the most common malignancy among women worldwide and is also known as the 2nd cause of mortality due to cancer in the United States (WHO, 2017). It was estimated annually 252,710 new cases of breast cancer and about 40,610 deaths in United States in 2017 (Siegel et al., 2017). In the two recent decades, the incidence of breast cancer has increased dramatically in Iranian women with a high risk of mortality (Mousavi et al., 2007). This increased risk may be linked with changing the pattern of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Analyze the reason: hypercapnia caused by breast cancer surgery, leading to increased body stress response, increased secretion of catecholamines and increased activity of the renin-angiotensin-aldosterone system, causing stress-related indicators such as HR, MAP, NE, and E increase [ 18 20 ]. Psychological intervention-assisted comfort nursing can reduce the anxiety of patients psychologically, improve their coping ability, meet the needs of patients from psychological, physical, and social aspects, and prompt them to deal with the stress of surgical trauma in a good psychological state [ 21 24 ]. In short, the clinical care pathway can reduce the perioperative stress response of patients with laparoscopic myomectomy and help patients to pass the perioperative period safely and steadily [ 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyze the reason: hypercapnia caused by breast cancer surgery, leading to increased body stress response, increased secretion of catecholamines and increased activity of the renin-angiotensin-aldosterone system, causing stress-related indicators such as HR, MAP, NE, and E increase [ 18 20 ]. Psychological intervention-assisted comfort nursing can reduce the anxiety of patients psychologically, improve their coping ability, meet the needs of patients from psychological, physical, and social aspects, and prompt them to deal with the stress of surgical trauma in a good psychological state [ 21 24 ]. In short, the clinical care pathway can reduce the perioperative stress response of patients with laparoscopic myomectomy and help patients to pass the perioperative period safely and steadily [ 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also common among Indonesian women who had positive experiences related to the support they have received, especially from mothers, grandmothers and mothers-inlaw [64], which is more obvious in the case of teenage mothers [65]. In this regard, it can be stated that spirituality positively intervenes in family relationships and in behaviors adopted during child-rearing [66][67][68]. The participants who depended on their family for support noted that this support included physical support during pregnancy, labor, and post-labor (for up to 40 days) as well as in initiating and maintaining breastfeeding [23].…”
Section: Discussionmentioning
confidence: 97%
“…Social sustenance received by women in their connection characterized by admiration and worth for their capabilities and expertise and by estimation to their information. However, Tilaki et al,2022, found that social sustenance linked, who said social sustenance linked with healthier mental adaptation and fewer mental indicators and recognized as a protective factor against unhappy affect and health results (35) . Also Holland & Holahan 2010, in their research found that perceived social sustenance linked with confident adaptation (36) .…”
Section: -Actual Study Of Data Collectionmentioning
confidence: 99%